Tracking via Square Grid of RFID Reader Positioning and Diffusion Algorithm - Reza, Ahmed Wasif; Tan, Kim Geok; Dimyati, Kaharudin (Springer US, 2011)
The study and analysis of RFID (radio frequency identification) reader positioning is important for RFID large-scale deployment. Therefore, the purpose of this research is to investigate the art of RFID reader positioning in order to develop a highly accurate positioning and tracking system for usage inside a building and also to optimize the tracking performance that can be applied to different active and passive RFID standards. This study involves design of square grid RFID reader network and position calculation using diffusion algorithm. Square grid network presents the solution of placement pattern of RFID readers, hence optimal number of required readers and guaranteed coverage can be achieved. The proposed diffusion algorithm makes use of distance information between the reader and the tag to estimate the RFID tag position. This study has also introduced a probabilistic mathematical model to maintain coverage of the unit square region and to ensure connectivity of the proposed square grid network. The effectiveness of the diffusion algorithm is evaluated in this study and the obtained results show satisfactory performance. The obtained results show that the proposed positioning system can achieve average positioning error below 1 m with different RFID reading ranges and in some cases accuracy improvement of about 65% can be reached than the results obtained by known positioning system. It is also found that the proposed diffusion algorithm together with square grid can bring approximately 50-85% improvement on raw accuracy provided by only square grid method.